2021
DOI: 10.3390/atmos12091199
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Promising Fenugreek (Trigonella foenum-graceum L.) Genotypes for Yield and Quality Characteristics in the Semiarid Climate of Turkey

Abstract: This study was conducted for two seasons from 2018 to 2020 to determine fenugreek genotypes yield and quality characteristics under semiarid climatic conditions. Fenugreek genotypes viz., Adana, Afghanistan, Gaziantep, Iraq, Kahramanmaraş, Kayseri, Mardin, Şanlıurfa with varieties of Berkem and Gürarslan were used as plant material in the research. Field trials were conducted with four replications according to the randomized complete block design. The results revealed that the time to emergence varied from 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The results of the current study were similar to [37] and [51]. However, differences in fenugreek fixed oil content between this study and [39] and [52] could be due to different environmental conditions, genetic variability, and growth conditions. This is because it has been reported that water stress changes seed composition and related qualities and decreases the fixed oil content of plants [53,54].…”
Section: Fixed Oil Content and Fatty Acid Profilessupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the current study were similar to [37] and [51]. However, differences in fenugreek fixed oil content between this study and [39] and [52] could be due to different environmental conditions, genetic variability, and growth conditions. This is because it has been reported that water stress changes seed composition and related qualities and decreases the fixed oil content of plants [53,54].…”
Section: Fixed Oil Content and Fatty Acid Profilessupporting
confidence: 85%
“…Our fixed oil content results were found to be higher under irrigated conditions (6.58-9.29%) and under dryland conditions (5.27-8.42%) than those of [39], who found that the fixed oil content of fenugreek ranged from 2.26 to 4.93% under different sowing times. Similarly, it was found that the fixed oil content ranged from 4.75 to 5.54% [51] and from 5.18 to 9.16% [52]. By contrast, it was noted that the fixed oil content of different fenugreek genotypes ranged from 2.17 to 15.52% [37] and that fenugreek fixed oil content ranged from 4.32% to 11.62% in fenugreek seeds [7].…”
Section: Fixed Oil Content and Fatty Acid Profilesmentioning
confidence: 99%
“…For example, it was reported that HFP was higher in cowpea plants grown under higher rainfall compared to dry seasons (Basaran et al, 2011). In contrast, sowing seeds in winter can cause over-watering, and in such conditions, HFP and PH were reported to be significantly reduced in lentil and fenugreek plants compared to more favourable seasons (Ahmad et al, 2021;Güzel and Özyazıcı, 2021). We can hypothesise that earlier events with stresses in plant growth can have a stronger reduction of HFP, whereas the later occurrence of stresses can have a lesser impact, since HFP is a trait of the bottom part of the stem which develops earlier.…”
Section: -29mentioning
confidence: 99%